An experimental assessment of landscape configuration effects on frog and toad abundance and diversity in tropical agro-savannah landscapes of southeastern Brazil - Silva, Fernando R.; Oliveira, Thiago A. L. [UNESP]; Gibbs, James P.; Rossa-Feres, Denise C. [UNESP] (Springer, 2012)
Amphibians are an imperiled group of vertebrate animals that typically have biphasic life histories involving a shift from aquatic larval habitats to terrestrial adult habitats. Habitat loss is the greatest threat to amphibians and the importance of the spatial configuration of terrestrial and breeding habitats upon the landscape in determining amphibian persistence is poorly known. The information gap is particularly acute in tropical landscapes that simultaneously host the greatest and most imperiled amphibian fauna on Earth. We installed 125 artificial ponds at different distances from forest fragments embedded in an agricultural matrix in southeastern Brazil. Constructed ponds attracted 13 anuran species; ponds at the forest fragment-matrix transition hosted a greater abundance and higher species richness of frogs and toads than those installed either far from or well within forest fragments. Forest fragments larger than 70 ha in agricultural areas harbored more individuals than smaller fragments. Our results indicate that landscape configuration has an important influence on frog and toad distribution and abundance in tropical agricultural landscapes and we suggest guidelines for maintaining favorable configurations of aquatic and terrestrial habitats for conserving this rich and imperiled species suite.
Keywords: Brazil; Frogs; Generalized linear mixed models; Isolation; Landscape; Seasonal semideciduous forest; Terrestrial habitats